Facing an eating disorder: A case of body dysmorphic disorder and avoidant/restrictive food intake disorder. (July 2022) - Milligan, Ty; Middleman, Amy B
Eating disorders can be notoriously difficult to diagnose and treat. This patient is an 18-year-old female who presents to care severely underweight and notably cachexic. For a number of years, she had experienced depressive symptoms, anxiety, and continued loss of appetite. She denied purposefully restricting foods, recognized that she was thin, and denied a fear of gaining weight. She was admitted to a disordered eating unit for refeeding and during her inpatient stay disclosed that she had a long-standing "hatred of face." Ultimately, she received the diagnoses of avoidant/restrictive food intake disorder and body dysmorphic disorder. This case highlights the importance of differentiating body dysmorphia, seen in body dysmorphic disorder, and distorted body image, as seen in anorexia nervosa. This differentiation is significant as the treatment approaches to these distinct diagnoses are not the same.